The effect of site-specific recombinases XerCD on the removal of over-replicated chromosomal DNA through outer membrane vesicles in bacteria - Mansky, Johannes; Wang, Hui; Wagner-Döbler, Irene; Tomasch, Jürgen (Microbiology spectrum, 2024)
Outer membrane vesicles (OMVs) are universally produced by Gram-negative bacteria and play important roles in symbiotic and pathogenic interactions. The DNA from the lumen of OMVs from the Alphaproteobacterium Dinoroseobacter shibae was previously shown to be enriched for the region around the terminus of replication ter and specifically for the recognition sequence dif of the two site-specific recombinases XerCD. These enzymes are highly conserved in bacteria and play an important role in the last phase of cell division. Here, we show that a similar enrichment of ter and dif is found in the DNA inside OMVs from Prochlorococcus marinus, Pseudomonas aeruginosa, Vibrio cholerae, and Escherichia coli. The deletion of xerC or xerD in E. coli reduced the enrichment peak directly at the dif sequence, while the enriched DNA region around ter became broader, demonstrating that either enzyme influences the DNA content inside the lumen of OMVs. We propose that the intra-vesicle DNA originated from over-replication repair and the XerCD enzymes might play a role in this process, providing them with a new function in addition to resolving chromosome dimers.IMPORTANCEImprecise termination of replication can lead to over-replicated parts of bacterial chromosomes that have to be excised and removed from the dividing cell. The underlying mechanism is poorly understood. Our data show that outer membrane vesicles (OMVs) from diverse Gram-negative bacteria are enriched for DNA around the terminus of replication ter and the site-specific XerCD recombinases influence this enrichment. Clearing the divisome from over-replicated parts of the bacterial chromosome might be a so far unrecognized and conserved function of OMVs.
Keywords: rekombinace genetická; DNA-nukleotidyltransferasy; rekombinasy; Escherichia coli; DNA repair; DNA; DNA replication; Integrases; proteiny z Escherichia coli; outer membrane vesicles; Recombination, Genetic; integrasy; DNA Nucleotidyltransferases; Escherichia coli Proteins; Recombinases